LONGITUDINAL CHANGES IN DENTAL ARCH CIRCUMFERENCE IN SULAIMANI CITY - Kareem, Fadil A.; Rasheed, Tara A.; Rauf, Aras M. (European Scientific Journal, ESJ, 2013)
Background: Evaluation of dental arches is of great importance for definitive diagnosis and optimal craniofacial treatment. The circumference or perimeter is the most important dimension of the dental arch and it changes according to age and gender. This issue hasn’t been conducted yet in sulaimani city; Aims: aim of the present study was to assess the dimensional changes in the dental arches occurring during the transitional period from mixed to permanent dentition in individuals with normal dentition. Methods: A group of fifty children with normal dentition aged 8-9 years were selected according to specific criteria in sulaimani city in kurdistan of iraq, dental arch dimensions were measured. Five years later, a second examination and measurement was performed to record the changes in dental arches. The data was analyzed by using statistical package for social sciences (SPSS, version 15) program for obtaining the descriptive statistics including the mean, and standard deviation, also the inferential statistics (t-test) was applied to test the significance difference between the dimensions. Results: The study showed an increase in the arch perimeter of the maxilla in the transition from mixed to permanent dentition for both males and females whereas in the lower arch it was the reverse. The arch perimeter differences between maxillary and mandibular arches show high significancy in both mixed and permanent dentitions P(0.00), P(0.00). There was asymmetry in the ach length between right and left side for both mixed and permanent dentition and most of the measurements of the permanent dentition showed high significant differences between right and left sides. There was a significant difference P(0.00) in maxillary and mandibular left and right incisor- canine distance (I-C) between males and females. Conclusion: Controlling the reduction of total arch length in the transition period from mixed dentition to permanent dentition may help in the early treatment of crowding of the teeth.